If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -5 = 3(x + -1(-2)) Reorder the terms: -5 + y = 3(x + -1(-2)) Multiply -1 * -2 -5 + y = 3(x + 2) Reorder the terms: -5 + y = 3(2 + x) -5 + y = (2 * 3 + x * 3) -5 + y = (6 + 3x) Solving -5 + y = 6 + 3x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + y = 6 + 5 + 3x Combine like terms: -5 + 5 = 0 0 + y = 6 + 5 + 3x y = 6 + 5 + 3x Combine like terms: 6 + 5 = 11 y = 11 + 3x Simplifying y = 11 + 3x
| 7x^2-7=y | | -7y(3)-3= | | 3x-5=190 | | 3x^2+18x+18=6 | | P(5-2n)=(5/6n)-(1/3) | | n(8n+4)=-4 | | x+54+5x=180 | | 4x+6+5x-5+100=180 | | -109=4(13b-12)+9b | | 6x-3/4=x-1 | | X/6=1.5 | | (3x1/10) | | Ln(3x+6)=ln(2x-1) | | 8-5q=3q+32 | | N/4=2.4 | | 10x^2-20x-9=-5x-6x | | 1/3=-4/x-8 | | N/4=3.1 | | -77=-11m-11(11-2m) | | R/5=2.4 | | 5+149=180 | | 2.4x=14.5 | | (1-x)(x+2)=0 | | -7(5x+2)=-399 | | y=(78-x)/2 | | X-5+2x+4=19 | | x=8-2(4) | | 10p+3= | | 25x+65=25x+23 | | -3/2x=5/6 | | -146=6(-6x+5)+4 | | 0=-3j+2 |